The Professional University Degree Of Actuary Through Bloom's Taxonomy - Arsuaga-Uriarte, Ainara; De la Peña Esteban, Iñaki; Garayeta-Bajo, Asier; Gómez-Pérez-Cacho, Olga; Moreno-Ruiz, Rafael; Trigo-Martínez, Eduardo (My University, 2022)
The aim of this paper is to determine the characteristics of the MScAFS in terms of how the Syllabus of the AAE sets out the subjects, organised into sub-areas, and the degree of development of the competences required to obtain the professional qualification of actuary in the EU. For this purpose, they are classified and quantified according to the type of conceptual development and the degree of in-depth study. This makes it possible to obtain the Master's degree graduate profile, which must coincide with the professional qualification agreed in the AAE. This profile is different from other master's degrees, whether complementary academic or with a research profile, and from other professions, which may or may not have one or more of the characteristics of the actuarial profession.
Keywords: Ciencias actuariales; Actuarial; Profession; Bloom's taxonomy; Master Degree in Actuarial Science